Biallelic MLH1 SNP cDNA expression or constitutional promoter methylation can hide genomic rearrangements causing Lynch syndrome. Issue 8 (28th June 2011) - Morak, Monika; Koehler, Udo; Schackert, Hans Konrad; Steinke, Verena; Royer-Pokora, Brigitte; Schulmann, Karsten; Kloor, Matthias; Höchter, Wilhelm; Weingart, Josef; Keiling, Cortina; Massdorf, Trisari; Holinski-Feder, Elke; et al.
Abstract : Background: A positive family history, germline mutations in DNA mismatch repair genes, tumours with high microsatellite instability, and loss of mismatch repair protein expression are the hallmarks of hereditary non-polyposis colorectal cancer (Lynch syndrome). However, in ∼10–15% of cases of suspected Lynch syndrome, no disease-causing mechanism can be detected. Methods: Oligo array analysis was performed to search for genomic imbalances in patients with suspected mutation-negative Lynch syndrome with MLH1 deficiency in their colorectal tumours. Results and conclusion: A deletion in the LRRFIP2 (leucine-rich repeat flightless-interacting protein 2) gene flanking the MLH1 gene was detected, which turned out to be a paracentric inversion on chromosome 3p22.2 creating two new stable fusion transcripts between MLH1 and LRRFIP2 . A single-nucleotide polymorphism in MLH1 exon 8 was expressed from both alleles, initially pointing to appropriate MLH1 function at least in peripheral cells. In a second case, an inherited duplication of the MLH1 gene region resulted in constitutional MLH1 promoter methylation. Constitutional MLH1 promoter methylation may therefore in rare cases be a heritable disease mechanism and should not be overlooked in seemingly sporadic patients.